2019
DOI: 10.1111/tbj.13373
|View full text |Cite
|
Sign up to set email alerts
|

The impact of the affordable care act on breast cancer care in the USA: A multi‐institutional analysis

Abstract: There are less data available on the effect of the ACA on breast cancer care beyond the screening level. A retrospective review at participating iCaRe2/BCCR institutions was completed before and after ACA. Post‐ACA, patients were older, more urban, and more likely to be insured through Medicaid. Increased imaging use was noted post‐ACA. These patients were less likely to be diagnosed with late‐stage cancers, received fewer mastectomies, and were more likely to have radiation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Although non-Medicaid expansion states like Alabama did not receive additional funding to expand women’s preventive services, many non-Medicaid expansion states still experienced an increase in insurance utilization following Medicaid-expansion, likely due to the increased awareness of insurance accessibility and importance of preventive healthcare initiatives popularized by the ACA [ 18 ]. In light of the central drive for Medicaid-expansion, if Alabama were to expand Medicaid, its citizens could experience increased insurance access and access to breast cancer screening modalities, incur lower incidences of late-stage breast cancer diagnoses, and become a more health-informed population [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although non-Medicaid expansion states like Alabama did not receive additional funding to expand women’s preventive services, many non-Medicaid expansion states still experienced an increase in insurance utilization following Medicaid-expansion, likely due to the increased awareness of insurance accessibility and importance of preventive healthcare initiatives popularized by the ACA [ 18 ]. In light of the central drive for Medicaid-expansion, if Alabama were to expand Medicaid, its citizens could experience increased insurance access and access to breast cancer screening modalities, incur lower incidences of late-stage breast cancer diagnoses, and become a more health-informed population [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…The Affordable Care Act, which provided screening services to noninsured women, has helped women in groups with less access to screening mammography services by removing the financial barrier of health insurance. One study showed that after the Affordable Care Act was implemented, there was a trend toward more non-White patients and urban residents accessing breast cancer care [48]. Another vulnerable group, those with mental illness, were actually demonstrated to access mammography more than their non-mentally ill counterparts, unless they were Medicaid beneficiaries, in which case they experienced significant disadvantages in breast cancer screening [49].…”
Section: Breast Cancer Screeningmentioning
confidence: 99%